Effect of mild aerobic exercise on the rehabilitation of lower limb injuries: A narrative review - Mohammad Akhoondian (Journal of Sports and Rehabilitation Sciences)
Lower limb injuries, including fractures, ligament tears, and stress-related conditions, significantly impact mobility and quality of life. If untreated, they can lead to chronic pain, joint instability, and muscle atrophy. Effective rehabilitation is crucial to restoring function and preventing long-term disability. Mild aerobic exercise, such as walking, cycling, and aquatic activities, has shown the potential to enhance recovery by improving blood circulation, muscle strength, and joint mobility. This review aims to evaluate the role of mild aerobic exercise in rehabilitating lower limb injuries, examining its physiological benefits and optimal implementation strategies. Findings indicate that mild aerobic exercise is crucial in rehabilitating lower limb injury. Aquatic exercises reduce limb swelling and improve muscle function due to hydrostatic pressure and resistance. Blood flow restriction techniques in aerobic training enhance muscle recovery while minimizing excessive strain. However, biomechanical asymmetry post-fatigue and the need for individualized exercise prescriptions remain considerations. Mild aerobic exercise is a safe and effective rehabilitation approach, improving mobility, reducing pain, and enhancing muscle strength. Personalizing exercise intensity and duration under professional supervision optimizes recovery outcomes. Future research should refine aerobic exercise protocols to maximize rehabilitation benefits and minimize risks.